2003
DOI: 10.1039/b212545e
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of alkyl derivatization methods for speciation of mercury based on solid phase microextraction gas chromatography with furnace atomization plasma emission spectrometry detection

Abstract: Access and use of this website and the material on it are subject to the Terms and Conditions set forth at A comparison of alkyl derivatization methods for speciation of mercury based on solid phase microextraction gas chromatography with furnace atomization plasma spectrometry detection Grinberg, P.; Campos, R. C.; Mester, Z.; Sturgeon, R.http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=fr L'accès à ce site Web et l'utilisation de son contenu sont assujettis aux conditions présentées dans le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…47 More recently, SPME has been applied to the determination of MMHg as an elegant, solvent-free sample extraction technique. 6,27,33,41,[48][49][50] The precision of results obtained using this technique is typically in the range of 2 to 10% RSD for MMHg.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 More recently, SPME has been applied to the determination of MMHg as an elegant, solvent-free sample extraction technique. 6,27,33,41,[48][49][50] The precision of results obtained using this technique is typically in the range of 2 to 10% RSD for MMHg.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently used procedures for the extraction of mercury species from solid samples are based on alkaline [2][3][4][5][6] and acidic leaching, 7,8 aqueous distillation, [9][10][11][12][13] supercritical fluid extraction 14 and microwave-assisted extraction. [15][16][17] Grignard reagents, [18][19][20][21] sodium tetraethylborate (NaBEt 4 ), 17,[22][23][24][25][26] sodium tetrapropylborate (NaBPr 4 ) 18,27 and sodium tetraphenylborate (NaBPh 4 ) [28][29][30][31][32][33] have been used for efficient derivatization. Gas chromatography, capillary electrophoresis or liquid chromatography are commonly used separation techniques for MMHg speciation in combination with atomic fluorescence spectrometry (AFS), 3,[34][35][36] electron-capture detection (GC-ECD), 37 atomic absorption spectrometry (AAS), 16,22 ion trap mass spectrometry, 30,31 inductively coupled plasma and microwave-induced plasma atomic emission spectrometry (ICP-AES, MIP-AES) …”
Section: Introductionmentioning
confidence: 99%
“…The ethylation process was investigated by several authors and found to be most effective in conditions where pH ranged between 4 and 6 [26,27]. This range was chosen for pH optimisation of the ethylation reaction employing BrMgEt 4 B.…”
Section: Ph Optimisationmentioning
confidence: 99%
“…However, the drawback of GC is that the species have to be rendered volatile and this requires a derivatisation step first with either Grignard reagents or more recently tetraalkyborate compounds [5] which can be time consuming and can sometimes result in species transformations [6], because of this another method for comparison is desirable. HPLC on the other hand requires no derivatisation step, as the species do not need to be volatile before injection 0003-2670/$ -see front matter © 2008 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%